The nucleosomes that mark centromere location on chromosomes old and new. Issue 1 (23rd April 2019) - Gambogi, Craig W.; Black, Ben E.
Abstract : Proper segregation of chromosomes is an essential component of cell division. The centromere is the locus at which the kinetochore—the proteinaceous complex that ties chromosomes to microtubules—forms during mitosis and meiosis. Thus, the centromere is critical for equal segregation of chromosomes. The centromere is characterized by both protein and DNA elements: the histone H3 variant CENP-A epigenetically defines the location of the centromere while centromeric DNA sequences are neither necessary nor sufficient for centromere function. Paradoxically, the DNA sequences play a critical role in new centromere formation. In this essay, we discuss the contribution of both epigenetics and genetics at the centromere. Understanding these contributions is vital to efforts to control centromere formation on synthetic/artificial chromosomes and centromere strength on natural ones.